Michel Foucault, Bruno Latour e algumas linhas de fuga na produção de conhecimentos - Simone Maria Hüning; Neuza Maria de Fátima Guareschi (Ciências Sociais Unisinos)
This article discusses some alterations that may be produced in the 'psy' field on the basis of Michel Foucault's and Bruno Latour's work by highlighting that in our view make this connection possible and fertile. Firstly, we gather questionings about the epistemological bases on which psychology has been founded in order to become scientific, as well as about the dichotomy between natural sciences and human sciences. Secondly, we turn our attention to Foucault's and Latour's works to discuss rituals of production and regulation of scientific discourses. In order to relate these authors' contributions to the 'psy' field, in the third part of this text we point out some strategies that make the political field visible in the production of knowledge and signal the necessary process of making explicit the network of interests that is involved in sciences. Finally, we redirect our look to psychology and the production of subjectivity, pointing out the close relationship between scientific production and the production of ways of living and governing.